(untitled) (Huellas, 2019)
The main aim of this work is to place the works that have a gender perspective within the scientific production of Argentine Geography, applying the methodology of Social Network Analysis. 1038 research articles published in 16 Geography journals between 2008 and 2018 were selected. The search of the articles was focused on four journal indexers: Latindex, Scielo, Redalyc and Directory Open Access Journal (DOAJ). The selection criteria were based on Geography journals in Argentina, with double indexing. With the key words of each article it was possible to build a network as a graph and to reach two main axes of discussion: 1) The position of centrality of topics such as ‘Territory’ and ‘Territorial Organization”; 2) The peripheral location of the research carried out on the topics of ‘Gender’ and ‘Sexualities’ in the Argentine Geography’.